(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aims to determine the degree to which cultural heritage is included in the content of the curricula of the first cycle of basic education. The content of the books (Social Studies, Arabic Language and Art Education) was selected for grades (4, 5, 6) as Sample analysis, The researcher used the content analysis methodology to achieve the previous aim. This requires the preparation of a list of areas of cultural heritage and its elements (levels) to be available in the content of the curricula of the first cycle, and use it as a tool for analysis after confirming its validity and reliabilityThe results were as follows:- For the content of the Social Studies curriculum: The degree of inclusion of cultural heritage in the fourth grade is high, as it reached 13.18%,in the fifth grade is intermediate (10.45%), and in the sixth grade is weak (4.70%).- For the content of the Arabic language curriculum: The degree of inclusion of the cultural heritage in the fourth grade is very weak, as it reached 1.43%, the fifth grade is very weak (3.88%),in the sixth grade (first grade) is high (12.66%),in (Second Semester) is also high (13.63%)- For the content of the art education curriculum: The degree of inclusion of the cultural heritage in the fourth grade is high, as it reached 12.18%, in the fifth grade is high (14.43%) and in the sixth grade is weak (7.75%).The researcher proposed to provide the authors of the curriculum with the list of cultural heritage fields and levels so that they include them in the curriculum in an integrated manner between the subjects and classes.